GFRα 1-2-3-4 co-receptors for RET Are co-expressed in Pituitary Stem Cells but Individually Retained in Some Adenopituitary Cells - Pradilla Dieste, Alberto; Chenlo, Miguel; Perez-Romero, Sihara; Garcia-Rendueles, Ángela R.; Suarez-Fariña, Maria; Garcia-Lavandeira, Montserrat; Bernabeu, Ignacio; Cameselle-Teijeiro, José Manuel; Alvarez, Clara V. (Frontiers in Endocrinology, 2020)
The RET tyrosine kinase receptor is expressed by the endocrine somatotroph cells of the pituitary where it has important functions regulating survival/apoptosis. However, RET is also expressed by the GPS pituitary stem cells localized in a niche between the adenopituitary and the intermediate lobe. To bind any of its four ligands, RET needs one of four co-receptors called GFRα1-4. It has been previously shown that GFRα1 is expressed by somatotroph cells and acromegaly tumors. GFRα2 was shown to be expressed by pituitary stem cells. GFRα4 was proposed as not expressed in the pituitary. Here we study the RNA and protein expression of the four GFRα co-receptors for RET in rat and human pituitary. The four co-receptors were abundantly expressed at the RNA level both in rat and human pituitary, although GFRα4 was the less abundant. Multiple immunofluorescence for each co-receptor and β-catenin, a marker of stem cell niche was performed. The four GFRα co-receptors were co-expressed by the GPS cells at the niche colocalizing with β-catenin. Isolated individual scattered cells positive for one or other receptor could be found through the adenopituitary with low β-catenin expression. Some of them co-express GFRα1 and PIT1. Immunohistochemistry in normal human pituitary confirmed the data. Our data suggest that the redundancy of GFRα co-expression is a self-supportive mechanism which ensures niche maintenance and proper differentiation.